Study on Pile-Soil Failure Mechanism in the Assessment of Aging Jacket Platform - Kolan De Velu, Bavani (Universiti Teknologi PETRONAS, 2013)

(untitled)
Pile foundation developed in offshore platforms must be able to resist the lateral loadings due to wind, wave and current forces subjected to the platform. Therefore, design of the pile foundation should satisfy the complicated and uncertain environmental magnitude. For a laterally loaded pile, the resistance depends on the bending moment capacity of the piles and also the interacting soil resistance. The pile must have adequate strength to resist the moment to prevent the deflection. The response of the pile foundation to the environmental load is strongly affected by pile structure and soil structure interaction. This paper aimed to study about the resistance of piles towards deflection caused by lateral forces. The non-linear approach or the p-y curve method is performed in this study to model and analyze the pile resistance towards lateral loadings. Structural Analysis Computer System (SACS) is used to model the required responses of pile foundation and also to perform the sensitivity analysis. Sensitivity analysis for certain design variables such as diameter, modulus of elasticity and yield strength was done and the results obtained shows the great impact of these parameters in the overall pile head deflections. Apart from that, a code comparison check was performed on the p-y approach for API 87, Modified Matlock, ISO 04, and DNV 80 using SESAM software.